P816 Functional rare variants influence the clinical response to anti-TNF therapy in Crohn's disease. (25th January 2019) - Chaparro, M; Aterido, A; Guerra, I; Iborra, M; Cabriada, J; Bujanda, L; Taxonera, C; García-Sánchez, V; Marín-Jiménez, I; Barreiro-de Acosta, M; Vera, I; Martín-Arranz, M; et al.
Abstract: Background: Loss-of-function (LoF) variants are one of the most interesting forms of rare functional genetic variations as they impair the function of a gene and are more likely to lead to extreme phenotypes. Our aim was to know the impact of functional rare variants in clinical response to anti-TNF therapy in Crohn's disease (CD). Methods: CD anti-TNF naïve patients starting anti-TNF treatment due to active disease (CDAI>150) were included. The whole genome was sequenced using the Illumina Hiseq4000 platform. Clinical response was defined as a CDAI score < 150 at Week 14 of anti-TNF treatment. Low-frequency variants were annotated and classified according to their damaging potential. The whole genome of CD patients was screened to identify homozygous LoF variants. The TNF signalling pathway was tested for overabundance of damaging variants using the SKAT-O method. Functional implication of the associated rare variation was evaluated using cell-type epigenetic enrichment analyses. Results: 41 CD patients were included -61% had remission and 24% were primary non-responders (Table 1); 3, 250 functional rare variants (2, 682 damaging and 568 LoF variants) associated with response to anti-TNF therapy were identified (Table 2). The strongest damaging impact was detected in 10 LoF SNPs (Table 3). Two homozygous LoF mutations were found in HLA-B and HLA-DRB1 genes associated with lack of response and remission, respectively. Genome-wide LoF variants were enriched in epigenetic marks specific for the gastrointestinal tissue (colon, p = 4.11e−4; duodenum, p = 0.011). The burden of damaging variation in the TNF signalling pathway was associated with response to anti-TNF drugs ( p = 0.018); damaging variants were enriched in epigenetic marks from CD8+ ( p = 6.01e−4) and CD4+ ( p = 0.032) T cells. Conclusions: Functional rare variants are involved in the response to anti-TNF therapy in CD. Cell-type enrichment analysis suggests that the gut mucosa and CD8+ T cells are the main mediators of this response. These findings provide new insights into the underlying heterogeneity of CD, revealing the basis of TNF-dependent biological mechanisms.